How to design renewable energy support policies with imperfect carbon pricing? - Wang, Ye; Cui, Xiao; Bu, Weisheng; Li, Li (Frontiers in Environmental Science, 2022)
Based on the emission trading scheme (ETS), this paper built a design framework of renewable energy support policies (RES), which is employed to assess the interaction mechanisms between feed-in tariffs (FIT) and ETS, renewable portfolio standards (RPS) and ETS. Based on the partial equilibrium model, taking the case of China electricity market, this paper quantitatively discussed the implementation effects of six different policy mix scenarios from three aspects: emission reduction, production of green electricity, and social welfare. According to the results, there were big differences among the implementation effects of different RES instruments based on ETS. The renewable subsidy policy, on the whole, is better than renewable portfolio standards in terms of emission reduction, but worse in terms of improving the production of green electricity. In addition, different from the renewable subsidy policy, the renewable portfolio standards can reduce social welfare. When the emission quota is easing, RES can be implemented to significantly improve social welfare. These simulation results inspire China for the design of effective energy policies.